Parkett : The Parkett series with contemporary artists (Zürich : Parkett-Verlag, 1996)
Table of Content Playing Pinball, Erwin Wurm’s Concept of Sculpture by Roland Wäspe No Exit by David Deitcher Richard Artschwager A Short History of the blp by Ingrid Schaffner Authentic Imitations of Genuine Replicas by Kurt W. Forster Surface Tension by Vik Muniz Cady Noland Holy Crusade by Lane Relyea Freak Shows and Talk Shows by Robert Bogdan Art as Encyclopedia, History as Vaudeville by Thyrza Nichols Goodeve Notes for an Index by Robert Nickas Hiroshi Sugimoto Sugimoto’s Metabolic Photography by Norman Bryson Half Dead by Ralph Rugoff Satori Among the Still Stills by Roger Denson John M. Armleder, Insert Öyvind Fahlström’s Final Manipulation by Daniel Birnbaum Gilles Deleuze, 1925 – 1995, Les Infos du Paradis by Robert Fleck Cartridge Music : Of Palimpsests and Parataxis, or How to Make a Mix, Cumulus from America by Paul D. Miller Art in Milan, Cumulus from Europe by Angela Vettese Humanity Transcended, A Book Review by Martin Heller
All three artists—Richard Artschwager, Cady Noland, Hiroshi Sugimoto—display a conspic-uously striking rigor of form, not as the familiar self-celebration of formalist provenance but rather as a pragmatic faith in the potential of form. While the rigor of the formalists unfolded through increased elision of the world, an opposite will is felt among these artists: Their extreme control of form feeds into the desire to involve as much of the world as possible. In the use of black and white, which plays a role in all three oeuvres, we recognize the meth¬od of abstraction, detachment, and reduction. Black and white may also signify crassness; morally it is the equivalent of good and evil. Comparison of the collaboration artists and their cultural embeddedness has been addressed by David Deitcher. (editorial by publisher)
boek
Keywords: Artschwager, Richard; Sugimoto, Hiroshi; Noland, Cady